Education disparities of Londrina-PR: what do the maps reveal us? - Omar Neto Fernandes Barros; Mirian Vizintim Fernandes Barros; Andrei Olak Alves; Igor F. Santini Zanatta (Geosul, 2008)
This text presents data on schools, education and income in the census sections of municipal site of Londrina-Paraná-Brazil, using the cartomatics program Philcarto. Individualized maps of the variables are presented and commented on and a hierarchical ascending classification, in 4 classes allowed to briefly represent the education diversity and income in the studied sections. The analysis variables were: schools (state, municipal and matters), resident people in the age group from 6 to 18 years, illiterates percentage, formed in the fundamental and graduate teaching and, strip of income (until 3 minimum wages, from 3 to 10, from 10 to 20 and superior to 20 minimum wages).